Revealing the biological features of the axolotl pancreas as a new research model - Ma, Hui; Peng, Guangcong; Hu, Yan; Lu, Binbin; Zheng, Yiying; Wu, Yingxian; Feng, Weimin; Shi, Yu; Pan, Xiangyu; Song, Li; Stützer, Ina; Liu, Yanmei; et al. (Frontiers in Cell and Developmental Biology, 2025)
IntroductionThe pancreas plays a crucial role in digestion and blood glucose regulation. Current animal models, primarily mice and zebrafish, have limited the exploration of pancreatic biology from an evolutionary-developmental perspective. Tetrapod vertebrate axolotl (Ambystoma mexicanum) serves as a valuable model in developmental, regenerative, and evolutionary biology. However, the fundamental biology of the axolotl pancreas remains underexplored. This study aims to characterize the unique developmental, functional, and evolutionary features of the axolotl pancreas to expand the understanding of pancreatic biology.MethodsWe conducted morphological, histological, and transcriptomic analyses to investigate the axolotl pancreas. Pancreatic development was observed using in situ hybridization and immunostaining for key pancreatic markers. RNA sequencing was performed to profile global gene expression during larva and adult stages. And differential gene expression analysis was used to characterize the conserved and unique gene patterns in the axolotl pancreas. Functional assays, including glucose tolerance tests and insulin tolerance tests, were optimized for individual axolotls. To assess pancreatic gene function, Pdx1 mutants were generated using CRISPR/Cas9-mediated gene editing, and their effects on pancreatic morphology, endocrine cell populations, and glucose homeostasis were analyzed.ResultsThe axolotl pancreas contains all known pancreatic cell types and develops from dorsal and ventral buds. Both of buds contribute to exocrine and endocrine glands. The dorsal bud produces the major endocrine cell types, while the ventral bud generates α and δ cells, but not β cells. Differential gene expression analysis indicated a transition in global gene expression from pancreatic cell fate commitment and the cell cycle to glucose response, hormone synthesis, and secretion, following the development progression. Notably, the adult axolotl pancreas exhibits slower metabolic activity compared to mammals, as evidenced by the results of GTT and ITT. The mutation of Pdx1 resulted in hyperglycemia and a significant reduction in pancreatic cell mass, including a complete loss of endocrine cells, although it did not lead to a lethal phenotype.DiscussionThis study examines the axolotl pancreas, highlighting the conservation of pancreatic development. Our study highlights the unique features of the axolotl pancreas and broadens the scope of animal models available for pancreatic evolution and disease research.